The Popularity of Karinding among Bandung Society - Daryana, Hinhin Agung (PANGGUNG, 2017)
ABSTRACT The study focuses on the impact of karinding popularity on Bandungnese. In trying to understand its focus, the study uses several approaches of social sciences such as sociology, anthropology, and qualitative research method including data collection from oral and written sources. Since karinding was played by a band called Karinding Attack, it became popular music in Bandung. In the end, the popularity of karinding gave some impacts on Bandungnese, both its practitioners and its audience. The movements considered as the result of karinding popularity include multiple activities such as tourism activities, networking development, educational activities, revitalization of traditional arts other than karinding, music development, literacy development, and the development of creative economy. Keywords: Impact, Popularity, Karinding, Bandung